Is the solution shown below correct? Explain.
9x+2=8X+6x
–8x² + 3x +2=0
-3+ (3) - (4)(-8)(2)
3
X =
-16
-37/9 (64)
-16
3+ 557
16

Respuesta :

Answer:

Solution is not correct.

Step-by-step explanation:

Given question is incomplete; Here is the complete question.

Is the solution shown in the attachment correct ?

9x + 2 = 8x² + 6x

We have to solve this equation with the help of quadratic formula,

-8x² + 9x + 2 = 6x

-8x² + 9x - 6x + 2 = 0

-8x² + 3x + 2 = 0

Quadratic formula of a standard quadratic equation (ax² + bx + c = 0) is,

x = [tex]\frac{-b\pm\sqrt{b^{2}-4ac}}{2a}[/tex]

By comparing our equation with the standard quadratic equation,

a = -8

b = 3

c = 2

By substituting the values of a, b and c in the quadratic formula,

x = [tex]\frac{-3\pm\sqrt{(3)^{2}-4(-8)(2)}}{2(-8)}[/tex]

x  = [tex]\frac{-3\pm\sqrt{9+64} }{-16}[/tex]

x  = [tex]\frac{9\pm\sqrt{73}}{16}[/tex]

Therefore, the given solution is not correct.

Ver imagen eudora

Answer:

Sample Response/Explanation

Step-by-step explanation:

No. The correct values of a, b, and c were substituted in, but the formula was simplified wrong. The 64 should be added so the radicand is 73. There should be 2 real roots.